SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA PROGRAM INDONESIA PINTAR SISWA MADRASAH DENGAN METODE SMART - Hari Moerti; Dedy Ardiansyah (LPPM ITB Yadika Pasuruan, 2026)
The Indonesia Pintar Program (PIP) for Madrasah is a government program for underprivileged students enabling them to continue their education without economic barriers. However, the current selection process at Madrasah Aliyah is manual, making it prone to subjectivity and inaccurate targeting. This study aims to develop a Decision Support System (DSS), implement the SMART method for criteria assessment, and generate objective and accurate recipient recommendations. Research data were sourced from students at MA Al-Arif, Gempol, Pasuruan, East Java. The Simple Multi Attribute Rating Technique (SMART) was utilized for attribute weighting in multi-attribute decision-making. Test results comparing manual and system calculations showed an accuracy rate of 99.3%, which indicates a very high level of computational consistency in processing the selection criteria. The study concludes that the implementation of a SMART-based DSS provides more objective, accurate, and targeted recommendations for PIP recipients at Madrasah Aliyah.